Kajian Penjadwalan Proyek Dengan Metode PERT - Fitriagita Fatika Putri, Andi; Sofyan Bachmid; Watono (Universitas Nusa Putra, 2025)
It is important to choose a scheduling method that is appropriate to the type and characteristics of a construction project in order to ensure the smooth running of a project. A project scheduling study is carried out which can consider probability aspects so that you can determine the level of accuracy in scheduling and the project completion time. The project case study studied was the Rongkong River Flood Control Development Project, North Luwu Regency, which experienced a delay of 7 days from the predetermined schedule, due to very high rainfall conditions at the construction project implementation location. This research was carried out using the PERT (Program Evaluation and Review Technique) method by reviewing research data in the form of work contracts, time schedules, RAB and monthly reports, to obtain the optimistic (a), pessimistic (b) and most likely (m) durations. The results of the study show that the PERT method can complete the Rongkong River Flood Control Development Project, North Luwu Regency, FY 2021 with a total expected time (TE) of 220 days faster than the planning schedule of 240 days, with a duration difference of 20 days faster than scheduling. existing. Based on the probability table, a planning schedule using PERT of 220 days only has a probability of project completion of 87.7%, while a planning schedule of 240 days has a greater probability of project completion with a probability of 90.1%. The results of this study show that PERT is not effective when used for scheduling. restart a project that is late.